Anti-Inflammatory Effect of Nicavet-2500 in Rodent Models of Acute Inflammation - David A. Areshidze; Lyudmila D. Timchenko; Igor V. Rzhepakovsky; Maria A. Kozlova; IaroslavnaA.Kusnetsova; Lyudmila A. Makartseva (Journal of Pharmacy and Nutrition Sciences, 2018)
This study examines the influence of the tissue preparation "NICAVET 2500" on an organism of mammals with use of rodent models of acute inflammation. It is established that action of a preparation leads to decrease in ESR. Hematologic and biochemical parameters also testify to anti-inflammatory action of "NICAVET 2500". Results of histological and morphometric research of a spleen and a thymus show processes of proliferation and migration of immunocytes, testifying to activization of immune reactions. In a thymus of rats of experimental group in comparison with control an increase in the dimensions of thymic lobules and also an increase in quantity of Hassal’s bodies, testifying to intensification of synthesis of the thymic hormones participating in process of an immunopoesis are revealed. As a result of the use of the preparation an increase of ability of an organism to resist alteration and also essential decrease in a level of development of inflammatory reaction of an organism are observed. The conducted research demonstrates the expressed immunomodulatory action of a preparation "NICAVET 2500" at an experimental model of inflammation.